Greek sanctuaries and temple architecture an introduction - Emerson, Mary (London Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"An introduction to ancient Greek sanctuary sites and temple architecture, explaining technical terms and aesthetic concepts behind Greek architectural design"
Introduction -- What was a sanctuary? -- From mud hut to marble temple: Doric and Ionic orders -- Architectural sculpture -- Delphi -- Olympia -- The Athenian Acropolis: historical background -- The Parthenon -- The Propylaia --The sanctuary of Athene Nike -- The Erechtheion -- The Hephaisteion -- Views and their meanings: the Acropolis and its surroundings -- The Sanctuary of Apollo Epikourios at Bassae -- The age of Greek expansion to the West: Paestum -- The Temple of Olympian Zeus at Acragas, Sicily -- Looking at art in sanctuaries
"First edition published by Gerald Duckworth & Co in 1997."-- title page verso
Includes bibliographical references (pages [257]-262) and index
Keywords: Temples -- Greece; Architecture, Ancient -- Greece; Architecture, Greek; Decoration and ornament, Architectural -- Greece; Sculpture, Greek; Sculpture, Ancient -- Greece; Greece -- Religious life and customs